A semi-solid pure aluminum battery electrolyte, a preparation method and application thereof

CN122889858APending Publication Date: 2026-10-09SHENZHEN HAINENG CHANGCHUAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611146173.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]基于上述现状,本发明的主要目的在于提供一种半固态纯铝电池电解质,解决了现有电池循环寿命不佳、容量保持率低以及安全性不高的问题

Benefits of technology

[0016]与现有技术相比,通过采用本发明半固态纯铝电池电解质制备电池,获得的电池具有超长循环寿命,即通过多重协同作用,电池在1C充放电条件下可实现≥15000次循环,容量保持率>80%;此外,获得电池具有高安全性,即半固态凝胶形态彻底杜绝了液态电解液漏液风险,且不可燃;另外,获得的电池具有优异倍率性能,即离子电导率高,支持大电流快速充放电。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889858A_ABST
    Figure CN122889858A_ABST
Patent Text Reader

Abstract

The application discloses a kind of semi-solid pure aluminum battery electrolyte and preparation method and application thereof, wherein, semi-solid pure aluminum battery electrolyte includes the following mass percentage components: polyvinyl alcohol 18~22%, alkali carbonate 6~10%, ionic liquid additive 12~18%, nano inorganic ion conductor 8~12%, interface control agent 2~5%, and the balance is deionized water.By using the semi-solid pure aluminum battery electrolyte of the application to prepare battery, the battery obtained has super-long cycle life, i.e., through multiple synergies, the battery can realize ≥15000 cycles under 1C charge-discharge conditions, and the capacity retention rate is >80%.In addition, the battery obtained has high safety, i.e., the semi-solid gel form completely eliminates the risk of liquid electrolyte leakage, and is not flammable.In addition, the battery obtained has excellent rate performance, i.e., high ionic conductivity, supporting large current fast charge-discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, specifically to a semi-solid pure aluminum battery electrolyte, its preparation method, and its application. Background Technology

[0002] With the development of renewable energy, the demand for long-life, low-cost energy storage technologies is becoming increasingly urgent. Aluminum batteries have attracted much attention due to their abundant raw materials, high safety, and high theoretical specific capacity. However, existing technologies suffer from the following bottlenecks: 1) Negative electrode corrosion and hydrogen evolution: Traditional aluminum batteries mostly use strongly alkaline electrolytes, leading to severe self-corrosion and hydrogen evolution reactions on the aluminum negative electrode. This not only consumes active materials but also causes battery bulging and failure; 2) Short cycle life: Due to uneven deposition and dendrite growth on the aluminum negative electrode surface, as well as the degradation of organic binders in the alkaline environment, the cycle life of existing aluminum batteries is typically only a few hundred to a few thousand times; 3) Limited rate performance: Liquid electrolytes are prone to leakage, and the ion transport kinetics are slow, limiting high-rate charge and discharge capabilities. Therefore, developing an electrolyte system that can inhibit corrosion, stabilize the interface, and achieve tens of thousands of cycles is a pressing technical problem that needs to be solved. Summary of the Invention

[0003] Based on the above situation, the main objective of this invention is to provide a semi-solid pure aluminum battery electrolyte that solves the problems of poor cycle life, low capacity retention, and low safety of existing batteries.

[0004] Another objective of this invention is to provide a semi-solid pure aluminum battery prepared using the above-described electrolyte.

[0005] Another objective of this invention is to provide a method for preparing the above-mentioned semi-solid pure aluminum battery electrolyte.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A semi-solid pure aluminum battery electrolyte comprises the following components by mass percentage: 18%~22% polyvinyl alcohol, 6%~10% basic carbonate, 12%~18% ionic liquid additive, 8%~12% nano-inorganic ionic conductor, 2%~5% interface modifier, and the balance being deionized water.

[0007] Preferably, the ionic liquid additive is a Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride in a molar ratio of (1.2~1.8):1.

[0008] Preferably, the basic carbonate is selected from at least one of basic copper carbonate and basic zinc carbonate.

[0009] Preferably, the nano-inorganic ionic conductor is a composite of polyethylene oxide and nano-alumina, wherein the nano-alumina has a particle size of 10-20 nm and a doping amount of 10%-15% of the mass of polyethylene oxide.

[0010] Preferably, the interface regulator is composed of lithium borate nanosheets and surface carboxyl-modified carbon quantum dots, wherein the thickness of the lithium borate nanosheets is less than 5 nm and the aspect ratio is greater than 100.

[0011] Preferably, the degree of polymerization of the polyvinyl alcohol is 1700-1800 and the degree of alcoholysis is greater than 98%.

[0012] Another technical solution of the present invention is as follows: a semi-solid pure aluminum battery, comprising a positive electrode, a negative electrode, a separator and the above-mentioned electrolyte; wherein, the negative electrode is pure aluminum or an aluminum alloy, and the positive electrode is a manganese-based oxide or an air electrode.

[0013] Preferably, the battery has a cycle life of more than 15,000 cycles at a 1C charge / discharge rate and a capacity retention rate of more than 80%.

[0014] The third technical solution of this invention is achieved as follows: the preparation method of the above-mentioned semi-solid pure aluminum battery electrolyte specifically includes the following steps: S1. Dissolve polyvinyl alcohol in deionized water, heat and stir to form a homogeneous solution; S2. Add the basic carbonate to the solution obtained in S1 and disperse it evenly; S3. Add the ionic liquid additive, nano-inorganic ionic conductor and interface regulator in sequence, and disperse by ultrasonication; S4. Vacuum degassing to obtain a semi-solid gel electrolyte.

[0015] Preferably, in step S3, the ultrasonic dispersion power is 300~500W and the time is 30~60min.

[0016] Compared with existing technologies, the battery prepared by using the semi-solid pure aluminum battery electrolyte of this invention has an ultra-long cycle life. That is, through multiple synergistic effects, the battery can achieve ≥15,000 cycles under 1C charge-discharge conditions with a capacity retention rate >80%. In addition, the battery has high safety, that is, the semi-solid gel form completely eliminates the risk of leakage of liquid electrolyte and is non-flammable. Furthermore, the battery has excellent rate performance, that is, high ionic conductivity, supporting high current fast charge and discharge. Attached Figure Description

[0017] The preferred embodiment of the electrophysiological monitoring system for scoliosis and spinal rehabilitation training according to the present invention will be described below with reference to the accompanying drawings. In the drawings: Figure 1This is a scanning electron microscope (SEM) image of the negative electrode material in the semi-solid pure aluminum battery obtained in Example 1 of the present invention. Figure 2 The time-voltage & current graph of the semi-solid pure aluminum battery obtained in Example 1 of the present invention during charge-discharge cycle testing; Figure 3 This is a capacity-voltage diagram of the semi-solid pure aluminum battery obtained in Example 1 of the present invention during charge-discharge cycle testing; Figure 4 This is a schematic diagram of the structure of the semi-solid pure aluminum battery obtained in Embodiment 1 of the present invention; Figure 5 This is a logic block diagram of the semi-solid pure aluminum battery electrolyte obtained in Embodiment 1 of the present invention. Detailed Implementation

[0018] To provide a more detailed description of the technical solutions of this application and to facilitate a better understanding of this application, specific embodiments of this application are described below in conjunction with the accompanying drawings. However, it should be understood that all illustrative embodiments and their descriptions are used to explain this application and do not constitute the sole limitation of this application.

[0019] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0020] Those skilled in the art will understand that the numerical ranges in the embodiments of the present invention should be understood to specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any stated value and an intermediate value within the stated range, as well as any other stated value or an intermediate value within the stated range, is also included within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0021] Unless otherwise stated, the technical / scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may be used in embodiments or test cases of the invention. All references to this specification are generally incorporated herein by reference to disclose and describe methods and / or materials associated with said references. In the event of any conflict with any incorporated reference, the contents of this application shall prevail.

[0022] It should be noted that all raw materials in the embodiments of the present invention were purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0023] The present invention provides a semi-solid pure aluminum battery electrolyte comprising the following components by mass percentage: 18%~22% polyvinyl alcohol, 6%~10% basic carbonate, 12%~18% ionic liquid additive, 8%~12% nano-inorganic ionic conductor, 2%~5% interface regulator, and the balance being deionized water.

[0024] The ionic liquid additive is a Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride in a molar ratio of (1.2~1.8):1; the basic carbonate is selected from at least one of basic copper carbonate and basic zinc carbonate; the nano-inorganic ionic conductor is a composite of polyethylene oxide and nano-alumina, wherein the nano-alumina has a particle size of 10~20 nm and a doping amount of 10%~15% of the mass of polyethylene oxide; the interface regulator is composed of lithium borate nanosheets and surface carboxyl-modified carbon quantum dots, wherein the thickness of the lithium borate nanosheets is less than 5 nm and the aspect ratio is greater than 100; the degree of polymerization of the polyvinyl alcohol is 1700~1800 and the degree of alcoholysis is greater than 98%.

[0025] This invention further provides a semi-solid pure aluminum battery, including a positive electrode, a negative electrode, a separator, and the electrolyte described above; wherein the negative electrode is pure aluminum or an aluminum alloy, and the positive electrode is a manganese-based oxide or an air electrode; the battery has a cycle life of more than 15,000 cycles at a 1C charge-discharge rate and a capacity retention rate of more than 80%.

[0026] The present invention further provides a method for preparing the above-mentioned semi-solid pure aluminum battery electrolyte, which specifically includes the following steps: S1. Dissolve polyvinyl alcohol in deionized water, heat and stir to form a homogeneous solution; S2. Add the basic carbonate to the solution obtained in S1 and disperse it evenly; S3. Add the ionic liquid additive, nano-inorganic ionic conductor and interface regulator in sequence, and disperse by ultrasonication; the ultrasonic dispersion power is 300~500W, and the time is 30~60min. S4. Vacuum degassing to obtain a semi-solid gel electrolyte.

[0027] The following are specific embodiments. Example 1

[0028] The semi-solid pure aluminum battery electrolyte provided in Example 1 of this invention comprises the following components: 20 g polyvinyl alcohol (degree of polymerization 1750), 8 g basic copper carbonate, 15 g Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) in a molar ratio of 1.5:1, 10 g polyepoxide (PEO) and nano-alumina (Al2O3) composite (containing 10 wt% Al2O3), 3 g lithium borate nanosheets (carbon quantum dots = 2:1), and the balance being deionized water.

[0029] The semi-solid pure aluminum battery electrolyte provided in Embodiment 1 of the present invention is obtained by the following method: 20g of polyvinyl alcohol (PVA, degree of polymerization 1750) was dissolved in 70g of deionized water and heated at 90℃ with stirring until completely dissolved; then 8g of basic copper carbonate was added and stirred evenly; subsequently, 15g of AlCl3-[EMIm]Cl (molar ratio 1.5:1), 10g of PEO-Al2O3 composite (containing 10wt% Al2O3) and 3g of interface regulator (lithium borate nanosheets: carbon quantum dots = 2:1) were added, and the mixture was ultrasonically dispersed at 500W for 40min and degassed under vacuum to obtain a semi-solid pure aluminum battery electrolyte.

[0030] The battery is assembled using the semi-solid pure aluminum battery electrolyte obtained in Example 1 of this invention, as detailed below: A CR2032 button cell was assembled by coating high-purity aluminum foil as the negative electrode, MnO2 as the positive electrode, and glass fiber as the separator with the above electrolyte.

[0031] The semi-solid pure aluminum battery obtained in Example 1 was tested, and the specific test methods and results are as follows: Charge-discharge tests were conducted at 25°C and a 1C rate. The results showed that the initial capacity was 120 mAh / g, and after 15,000 cycles, the capacity retention was 82.6%, the coulombic efficiency remained stable at over 99.3%, and no obvious hydrogen evolution was observed.

[0032] The stability of the negative electrode in the semi-solid pure aluminum battery obtained in Example 1 of this invention was tested (stability of the pure aluminum negative electrode interface and verification of the absence of dendrites). (1) Test method: Voltage polarization stability test: Using the semi-solid-state battery obtained in Example 1 of this invention as the test object, under constant temperature of 25℃, the voltage polarization stability test was conducted at 0.1 mA / cm². 2 The constant current was continuously charged and discharged for 100 h, and the steady-state polarization voltage fluctuation difference on the negative electrode side was recorded in real time to characterize the stability of the negative electrode interface. Dendrite morphology observation: After completing the long-term polarization test, the battery cell was disassembled in an argon-filled glove box. The negative electrode surface was cleaned with DMC solvent and vacuum dried. The microstructure of the Mg-Al alloy negative electrode surface was observed using a scanning electron microscope (SEM); see details below. Figure 1 , Figure 1 This is a scanning electron microscope image of the negative electrode material. Analysis... Figure 1 It is evident that the surface of the negative electrode material is dendrite-free, thus laying a solid foundation for the fabrication of high-performance batteries.

[0033] Example 2 The semi-solid pure aluminum battery electrolyte provided in Example 2 of this invention comprises the following components: 20 g polyvinyl alcohol (degree of polymerization 1750), 8 g basic zinc carbonate, 15 g Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) in a molar ratio of 1.2:1, 10 g polyepoxide (PEO) and nano-alumina (Al2O3) composite (containing 10 wt% Al2O3), 3 g lithium borate nanosheets (carbon quantum dots = 2:1), and the balance being deionized water.

[0034] The semi-solid pure aluminum battery electrolyte provided in Embodiment 2 of the present invention is obtained by the following method: 20g of PVA (degree of polymerization 1750) was dissolved in 70g of deionized water and heated at 90℃ with stirring until completely dissolved; then 8g of basic zinc carbonate was added and stirred evenly; subsequently, 15g of AlCl3-[EMIm]Cl (molar ratio 1.2:1), 10g of PEO-Al2O3 composite (containing 10wt% Al2O3) and 3g of interface regulator (lithium borate nanosheets: carbon quantum dots = 2:1) were added, and the mixture was ultrasonically dispersed at 500W for 40min and degassed under vacuum to obtain a semi-solid pure aluminum battery electrolyte.

[0035] The battery is assembled using the semi-solid pure aluminum battery electrolyte obtained in Example 2 of this invention, as detailed below: A CR2032 button cell was assembled by coating high-purity aluminum foil as the negative electrode, MnO2 as the positive electrode, and glass fiber as the separator with the above electrolyte.

[0036] The battery obtained in Example 2 was tested, and the specific test methods and results are as follows: Charge-discharge tests were conducted at 25°C and a 1C rate. The results showed that the initial capacity was 120 mAh / g, and after 15,000 cycles, the capacity retention was 81.2%, the coulombic efficiency remained stable at over 99.3%, and no obvious hydrogen evolution was observed.

[0037] Example 3 The semi-solid pure aluminum battery electrolyte provided in Example 3 of this invention comprises the following components: 20 g polyvinyl alcohol (degree of polymerization 1750), 8 g basic copper carbonate, 15 g Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) in a molar ratio of 1.8:1, 10 g polyepoxide (PEO) and nano-alumina (Al2O3) composite (containing 10 wt% Al2O3), 3 g lithium borate nanosheets (carbon quantum dots = 2:1), and the balance being deionized water.

[0038] The semi-solid pure aluminum battery electrolyte provided in Embodiment 3 of the present invention is obtained by the following method: 20g of PVA (degree of polymerization 1750) was dissolved in 70g of deionized water and heated at 90℃ with stirring until completely dissolved; then 8g of basic zinc carbonate was added and stirred evenly; subsequently, 15g of AlCl3-[EMIm]Cl (molar ratio 1.2:1), 10g of PEO-Al2O3 composite (containing 12wt% Al2O3) and 3g of interface regulator (lithium borate nanosheets: carbon quantum dots = 2:1) were added, and the mixture was ultrasonically dispersed at 500W for 40min and degassed under vacuum to obtain a semi-solid pure aluminum battery electrolyte.

[0039] The battery is assembled using the semi-solid pure aluminum battery electrolyte obtained in Example 3 of this invention, as detailed below: A CR2032 button cell was assembled by coating high-purity aluminum foil as the negative electrode, MnO2 as the positive electrode, and glass fiber as the separator with the above electrolyte.

[0040] The battery obtained in Example 3 was tested, and the specific test methods and results are as follows: Charge-discharge tests were conducted at 25°C and a 1C rate. The results showed that the initial capacity was 120 mAh / g, and after 15,000 cycles, the capacity retention was 82.1%, the coulombic efficiency remained stable at over 99.3%, and no obvious hydrogen evolution was observed.

[0041] Example 4 The semi-solid pure aluminum battery electrolyte provided in Example 4 of this invention comprises the following components: 20 g polyvinyl alcohol (degree of polymerization 1750), 8 g basic copper carbonate, 15 g Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) in a molar ratio of 1.5:1, 10 g polyepoxide (PEO) and nano-alumina (Al2O3) composite (containing 10 wt% Al2O3), 3 g lithium borate nanosheets (carbon quantum dots = 2:1), and the balance being deionized water.

[0042] The semi-solid pure aluminum battery electrolyte provided in Embodiment 4 of the present invention is obtained by the following method: 20g of PVA (degree of polymerization 1750) was dissolved in 70g of deionized water and heated at 80℃ with stirring until completely dissolved; then 8g of basic copper carbonate was added and stirred evenly; subsequently, 15g of AlCl3-[EMIm]Cl (molar ratio 1.5:1), 10g of PEO-Al2O3 composite (containing 10wt% Al2O3) and 3g of interface regulator (lithium borate nanosheets: carbon quantum dots = 2:1) were added, and the mixture was ultrasonically dispersed at 400W for 30min and degassed under vacuum to obtain a semi-solid pure aluminum battery electrolyte.

[0043] The battery is assembled using the semi-solid pure aluminum battery electrolyte obtained in Example 4 of this invention, as detailed below: A CR2032 button cell was assembled by coating high-purity aluminum foil as the negative electrode, MnO2 as the positive electrode, and glass fiber as the separator with the above electrolyte.

[0044] The battery obtained in Example 4 was tested, and the specific test methods and results are as follows: Charge-discharge tests were conducted at 25°C and a 1C rate. The results showed that the initial capacity was 120 mAh / g, and after 15,000 cycles, the capacity retention was 80.9%, the coulombic efficiency remained stable at over 99.3%, and no obvious hydrogen evolution was observed.

[0045] Example 5 The semi-solid pure aluminum battery electrolyte provided in Example 5 of this invention comprises the following components: 20 g polyvinyl alcohol (degree of polymerization 1750), 8 g basic copper carbonate, 15 g Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) in a molar ratio of 1.5:1, 10 g polyepoxide (PEO) and nano-alumina (Al2O3) composite (containing 10 wt% Al2O3), 3 g lithium borate nanosheets (carbon quantum dots = 2:1), and the balance being deionized water.

[0046] The semi-solid pure aluminum battery electrolyte provided in Embodiment 5 of the present invention is obtained by the following method: 20g of PVA (degree of polymerization 1750) was dissolved in 70g of deionized water and heated at 100℃ with stirring until completely dissolved; then 8g of basic copper carbonate was added and stirred evenly; subsequently, 15g of AlCl3-[EMIm]Cl (molar ratio 1.5:1), 10g of PEO-Al2O3 composite (containing 10wt% Al2O3) and 3g of interface regulator (lithium borate nanosheets: carbon quantum dots = 2:1) were added, and the mixture was ultrasonically dispersed at 300W for 60min and degassed under vacuum to obtain a semi-solid pure aluminum battery electrolyte.

[0047] The battery is assembled using the semi-solid pure aluminum battery electrolyte obtained in Example 5 of this invention, as detailed below: A CR2032 button cell was assembled by coating high-purity aluminum foil as the negative electrode, MnO2 as the positive electrode, and glass fiber as the separator with the above electrolyte.

[0048] The battery obtained in Example 5 was tested, and the specific test methods and results are as follows: Charge-discharge tests were conducted at 25°C and a 1C rate. The results showed that the initial capacity was 120 mAh / g, and after 15,000 cycles, the capacity retention was 80.6%, the coulombic efficiency remained stable at over 99.3%, and no obvious hydrogen evolution was observed.

[0049] Comparative Example 1 The difference between Comparative Example 1 and Example 1 of the present invention is that the comparative example uses a traditional KOH aqueous solution + PVA system, while the other process parameters are the same as those in Example 1.

[0050] Test results: After 300 cycles, the capacity decreased to less than 50%, the negative electrode was severely corroded, and the battery bulged.

[0051] Furthermore, the charging capacity, discharging capacity, coulombic efficiency, and median voltage of the semi-solid pure aluminum battery obtained by this invention were tested: (1) Test method: The batteries obtained in Examples 1-5, as well as the batteries obtained in Comparative Example 1 and Comparative Document 2, were tested using the Blue Battery Test System (BTSDA 7.6.0.425). The test conditions were set as follows: 10C constant current and constant voltage charging (cutoff current 0.02C), followed by 1C constant current discharge to the cutoff voltage.

[0052] (2) Test results: The charging time was about 18 minutes and the discharging time was about 30 minutes. Other test results are shown in Table 1.

[0053] Table 1. Battery performance test data obtained from each embodiment and comparative example.

[0054] Test results show that the charging time is approximately 18 minutes, the discharging time is approximately 30 minutes, and other test results are as follows: Figure 2 , Figure 3 As shown in Table 1, the test results show that the semi-solid pure aluminum battery provided in this embodiment has an ultra-long cycle life. After more than 15,000 charge-discharge cycles, the capacity retention rate is still close to 100%, and the charge-discharge efficiency is stable at more than 99.5%, which far exceeds the level of existing solid-state batteries. The median voltage is around 1.26V, which significantly shortens the charging time.

[0055] In summary, the battery prepared using the semi-solid pure aluminum battery electrolyte of this invention has an ultra-long cycle life, namely, through multiple synergistic effects, the battery can achieve >15,000 cycles under 1C charge-discharge conditions with a capacity retention rate of >80%; in addition, the obtained battery has high safety, namely, the semi-solid gel morphology completely eliminates the risk of leakage of liquid electrolyte and is non-flammable; furthermore, the obtained battery has excellent rate performance, namely, high ionic conductivity, supporting high-current rapid charge-discharge.

[0056] Therefore, it can be seen that this invention, through its innovative semi-solid electrolyte formula, successfully solves the inherent lifespan limitation of pure aluminum batteries, achieving industry-leading technical indicators and possessing extremely high commercial value.

[0057] It should be understood that the above embodiments are merely exemplary and not restrictive. Various obvious or equivalent modifications or substitutions that can be made by those skilled in the art regarding the above details without departing from the basic principles of the present invention will be included within the scope of the claims of the present invention.

Claims

1. A semi-solid pure aluminum battery electrolyte, characterized in that, It includes the following components by mass percentage: polyvinyl alcohol 18%~22%, basic carbonate 6%~10%, ionic liquid additive 12%~18%, nano-inorganic ionic conductor 8%~12%, interface modifier 2%~5%, and the balance is deionized water.

2. The semi-solid pure aluminum battery electrolyte according to claim 1, characterized in that, The ionic liquid additive is a Lewis acidic ionic liquid formed by AlCl3 and 1-ethyl-3-methylimidazolium chloride in a molar ratio of (1.2~1.8):

1.

3. The semi-solid pure aluminum battery electrolyte according to claim 1, characterized in that, The basic carbonate is selected from at least one of basic copper carbonate and basic zinc carbonate.

4. The semi-solid pure aluminum battery electrolyte according to claim 1, characterized in that, The nano-inorganic ionic conductor is a composite of polyethylene oxide and nano-alumina, wherein the nano-alumina has a particle size of 10~20nm and a doping amount of 10%~15% of the mass of polyethylene oxide.

5. The semi-solid pure aluminum battery electrolyte according to claim 1, characterized in that, The interface regulator is composed of lithium borate nanosheets and surface carboxyl-modified carbon quantum dots. The lithium borate nanosheets have a thickness of less than 5 nm and an aspect ratio of greater than 100.

6. The semi-solid pure aluminum battery electrolyte according to any one of claims 1-5, characterized in that, The degree of polymerization of the polyvinyl alcohol is 1700~1800, and the degree of alcoholysis is greater than 98%.

7. A semi-solid pure aluminum battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte as described in any one of claims 1 to 6; wherein the negative electrode is pure aluminum or an aluminum alloy, and the positive electrode is a manganese-based oxide or an air electrode.

8. The semi-solid pure aluminum battery according to claim 7, characterized in that, The battery has a cycle life of more than 15,000 cycles at a 1C charge / discharge rate and a capacity retention rate of more than 80%.

9. A method for preparing a semi-solid pure aluminum battery electrolyte according to any one of claims 1-6, characterized in that, The method specifically includes the following steps: S1. Dissolve polyvinyl alcohol in deionized water, heat and stir to form a homogeneous solution; S2. Add the basic carbonate to the solution obtained in S1 and disperse it evenly; S3. Add the ionic liquid additive, nano-inorganic ionic conductor and interface regulator in sequence, and disperse by ultrasonication; S4. Vacuum degassing to obtain a semi-solid pure aluminum battery electrolyte.

10. The method for preparing a semi-solid pure aluminum battery electrolyte according to claim 9, characterized in that, In step S1, the heating and stirring temperature is 80~100℃; in step S3, the ultrasonic dispersion power is 300~500W and the time is 30~60min.